PERAN MANAJEMEN KURIKULUM TERPADU DALAM MEMBANGUN KARAKTER DAN KOMPETENSI SANTRI - Sari Andini; Bintang Ridzky Dwi Putra; Rasyita Dewi Lubis; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to explore educational innovation in Islamic boarding schools in order to build a superior and competitive generation. Using a qualitative approach and case study design, this research analyzes innovative strategies implemented in several selected Islamic boarding schools in Indonesia. Research findings show that these Islamic boarding schools have made various innovations in the curriculum by integrating the national and traditional curriculum, as well as utilizing technology in the learning process. Apart from that, developing soft skills through comprehensive training programs and adopting an active learning approach is the main focus in efforts to improve students' competency. Collaboration with various parties, including higher education institutions and the industrial sector, also expands the network and resources available to Islamic boarding schools. These innovations have a positive impact on improving the academic, religious, and social, emotional and intellectual abilities of students, so that they are able to compete in the global job market. However, this research also identified challenges faced by Islamic boarding schools, such as limited resources and resistance to change from several parties within the Islamic boarding schoolThis article discusses the important role of integrated curriculum management in developing the character and competence of students in Islamic boarding schools. Islamic boarding schools have a strategic role in Islamic education in Indonesia, becoming the foundation for the formation of knowledgeable, noble, and independent scholars. Curriculum integration between the Islamic boarding school curriculum and the government curriculum is considered crucial in increasing the efficiency and effectiveness of Islamic boarding school education. Integrated curriculum management includes planning, implementation, and control as the key to ensuring systematic and sustainable curriculum implementation. This study uses a qualitative literature study approach to investigate the impact of curriculum integration on the development of the character and competence of students. The results show that this approach not only improves the academic competence of students but also strengthens character values ​​and practical skills, which are important foundations for facing global challenges and preparing students to become responsible and competent members of society.